Incremental Concentrations of Tacrolimus Eye Drops as a Strategy for the Management of Severe Vernal Keratoconjunctivitis - Albarry, Maan Abdullah; Parekh, Mohit; Ferrari, Stefano; Eltahir, Heba Mahmoud; Shehata, Ahmed M; Shaker, Mohamed A; Elbadawy, Hossein Mostafa (Frontiers in Pharmacology, 2022)
Purpose: To assess the effect of different concentrations of Tacrolimus eye suspension on the epithelium and stromal ‎keratocytes of human corneas and to investigate whether it can be safely used for severe cases of Vernal ‎Keratoconjunctivitis (VKC).‎ Methods: Tacrolimus eye suspension was prepared in a range of concentrations; 0.005%, 0.01%, 0.05%, 0.1% and ‎‎0.2%. Molecular analysis was performed ex vivo on human corneas (n=18) obtained from the eye bank. Transparency ‎and thickness of each cornea was measured while Live/Dead staining was performed using triple labeling assay. ‎Incremental concentration approach was then tested on 3 severe cases of VKC. ‎ Results: All tested Tacrolimus concentrations showed no significant changes in corneal thickness or transparency. In ‎corneas treated with 0.1%, rare scattered dead cells were observed, while the folds of corneal surfaces were mostly ‎viable, unlike concentrations higher than 0.1% and lower than 0.05%. Stromal cell densities were highest in 0.1% ‎Tacrolimus treatment condition. Incremental concentrations of Tacrolimus suspension was shown to significantly ‎improve VKC cases, where the concentration used for each case depended on the severity of the case. ‎ Conclusions: Topical administration of Tacrolimus was not toxic to human corneal cells at all tested concentrations ‎and the 0.1% concentration has shown the best viability of the corneal tissue. Tacrolimus eye suspension was shown ‎to be safe and effective for use in severe VKC and is proposed as a topical ocular immunosuppressant drug enabling ‎clinicians to incrementally increase the drug concentration in according to the clinical severity of the disease to ‎achieve the optimal therapeutic response.‎